STIMULATING CHILDREN'S CREATIVITY: IMPLEMENTATION OF THE DESIGN, EXPLAIN, DEVELOP, AND EVALUATION-PROJECT BASED LEARNING (DEDEN-PJBL) MODEL IN KINDERGARTEN (THUFULA, 2024)
This study examines the implementation of the Design, Explain, Develop, and Evaluation-Project-based Learning (DEDEn-PjBL) model in stimulating creativity among children aged 5-6 years in two kindergartens in Makassar City, using a mixed-methods approach. Employing an embedded concurrent design, 30 participants were involved in project-based learning activities using the DEDEn-PjBL model. This model encompasses the Design, Explanation, Development, and Evaluation phases to foster creativity. Data were collected through educator interviews, project observations, and quantitative assessments of children’s creative development using standardised rating scales from the Ministry of Education and Culture. The validity of the collected information was verified using source triangulation techniques. The findings indicate a significant increase in creativity in terms of fluency, flexibility, originality, and elaboration. The children designed their projects using pre-prepared materials and tools, resulting in a 33.33% improvement to the “Developing as Expected” category and a 66.66% improvement to the “Developing Very Well” category. This study recommends incorporating the DEDEnPjBL model into the curriculum, as it significantly enhances creativity. However, the study is limited to two kindergartens, thus its findings cannot be widely generalised. Additionally, the short implementation period may not be sufficient to observe the long-term effects of the DEDEn-PjBL model.